Target-like Pigmentation After Minipunch Grafting in Stable Vitiligo - Bisen, Nelee (Medknow Publications & Media Pvt Ltd, 2014)
Surgical treatment for vitiligo has been ever evolving. Each surgical modality has its own benefits and limitations. Miniature punch grafting is the most extensively performed surgery, which gives good results in stable vitiligo. Herein we report an unusual type of repigmentation observed after minipunch grafting in a patient of stable vitiligo, which resembled target-like lesions with a “perigraft halo” surrounding individual grafts. Such pigment spread occurred despite the use of 0.5 mm larger graft from the donor site.